Utilizing Vocabulary Journals to Enhance Junior High School Students' Understanding and Employment of Vocabulary in Maluku Barat Daya - Lidiporu, Hefriantini; Meyer, Fredi; Kamanasa, Louisa Sarah (Yayasan Pendidikan Internasional Bengkulu, 2024)
This research examines the utilizing of vocabulary journal in junior high school students. Vocabulary learning is crucial part in learning a language because it contains the basic knowledge to comprehend a language. Identified challenges primarily revolve around the strategies in classroom, the use of materials, and the vocabulary learning technique. Resource constraints encompass limited teaching materials and how to be more comprehensive in vocabulary learning. To address this challenges, the articles outlines the utilizing of vocabulary journals to comprehend the understanding and employment of vocabulary learning. Additionally, the article explores the best practices in utilizing vocabulary journal. This library research aims to contribute valuable insights to educator, policymakers, and researchers involved in the implementation of English language teaching and learning.